Qualitative Analysis of Borax (Sodium Tetraborate) Content in Meatballs in Pidie Regency - Aliya Najiba; Arif Sardi; Diannita Harahap (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Food safety in street foods remains a serious challenge in Indonesia due to the widespread misuse of hazardous chemicals. This study aims to identify the presence of borax in food samples circulating in the community. A descriptive qualitative method was applied to 48 samples collected through purposive sampling across 12 sub-districts, with analysis conducted via the rosocyanine complex formation test. The results showed that 22 samples (45.8%) tested positive for borax, characterized by a color change to reddish-brown. These findings indicate that nearly half of the samples do not comply with the food safety standards set by BPOM Regulation No. 22 of 2023. Consequently, urgent intervention by relevant authorities is required to enhance consumer protection and ensure the distribution of safe food products within the region.